Reducing everyday consumption: Mapping the landscape of grassroots social movements and activist households in Australia. (September 2022) - Thredgold, Charmaine J.; Daniel, Lyrian; Baker, Emma
Abstract: Increasing numbers of relatively affluent people are endeavoring to reduce everyday consumption and waste in response to environmental and social concerns. This paper explores five activist lifestyles and grassroots social movements that aim to reduce everyday consumption to uncover who, why, what and how households reduce consumption. Our understanding of everyday consumption captures the design of the house, the physical dwelling and the experience of day-to-day living. We seek to understand the lifestyle and identity characteristics, motivations, barriers, meanings and cultural beliefs that influence social norms towards less consumption. Our review reveals that most people begin from raised consciousness and concern about production and consumption practices. Evidence is building that shows, for many people, living a less consumptive, more collaborative, simple, frugal, downshifted life is beneficial to human health and well-being and highlights part of the success of these movements and lifestyles. Activist lifestyles should be promoted to a relatively affluent public as creative, meaningful, and satisfying and not as sacrifices to be made. This central finding offers a potentially useful behavioral lever to complement structural level sustainable urban transitions.